Customer Satisfaction Analysis By Integrating Service Quality (Servqual) Methods And Importance Performance Analysis: Analisis Kepuasan Pelanggan Dengan Mengintegrasikan Metode Kualitas Layanan (Servqual) Dan Analisis Kinerja Penting - Slamet, Mukhammad; Sulistiyowati, Wiwik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the indicators that affect the quality of service for the company. Service quality analysis is carried out by integrating the Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. Servqual is a method that identifies service quality using five dimensions: tangible, reliability, responsiveness, assurance, and empathy. Each dimension in the deployment becomes several indicators that describe the moment of truth of the quality of service the company provides to consumers. The results of the measurement of service quality have then measured the relationship between consumer perceptions and priorities for improving service quality which is translated through the analysis quadrant. Each quadrant of analysis has its own meaning. The results of this study indicate that the attributes found in quadrant 1 to be a priority for improvement are the service (administrative) patience indicator in listening to consumer complaints contained in the assurance dimension with a satisfaction level value of 4,086 points and an importance level value of 4,114 points